FOUR NEW RECORDS OF THE GENUS PYRUS (ROSACEAE) FROM PAKISTAN - M. Islam; H. Ahmad; J. Alam; H. Ali; M. Fahim; M. Hanif (Journal of Animal and Plant Sciences, 2019)
The objectives of the present study were to explore, identify and document Pyrus (pears) species from Pakistan, their screening and recommendation for further breeding program. Extensive surveys were conducted during 2010-2011 to identify and document Pyrus (Pears) from Pakistan. Plant specimens were collected, processed and identified. Using established floristic keys for different countries and literature, four new records of the genus Pyrus L.(Rosaceae) viz., P. ussuriensis, P. armeniacifolia, P. hopeiensis and P. communis are reported for the flora of Pakistan. The detailed morphological description, flowering and fruiting duration, ecological notes, distribution, GPS coordinates, altitudes and voucher specimens of the taxa are reported in this paper, along with images, distribution map and a table of comparative differentiating characters of these taxa.
Keywords: New Records; Pyrus (Pears); Rosaceae; Pakistan